Profil Kemampuan Literasi Kuantitatif dan Kualitas Argumentasi Siswa pada Konsep Biologi - Melati Fitriani (Al Jahiz: Journal of Biology Education Research, 2022)
As one of the basic skills in an effort to develop the quality of human resources in the 21st century, this research based on the development of quanti tative literacy capability and argumentation through biology learning. This study is a preliminary study to analyze students 'early capability of quantitative literacy and high school students' argumentation through their profiles. The research subjects involved were 37 students of 12th grade MIPA. This research was conducted in Islamic Senior High School 2 Lebak by using purposive sampling technique. The research data were collected using a description test that measured quantitative literacy capability with four indicators (interpretation, representation, calculation, and analysis), while the quality of argumentation with written argumentation. Instruments used in quantitative literacy questions refer to the assessment rubric of the Association of American Colleges and Universities (AAC & U) and consists of four essay questions covering one indicator on each question. The instruments used in the argumentation problem refers to Sandoval & Millwood for the aspect of argumentation and Erduran for the level of argumentation which consists of three essay questions that cover aspects of conceptual quality and epistemic quality aspects. The results of preliminary study of achievement of each indicator on quantitative literacy capability indicate that the percentage of students who reach level 2 (Milestones) more than other level with details: interpretation (56.8%), representation (48.6%), calculation (59.5%), the most dominant analysis is Level 1 (73%). Furthermore, the results of argumentation test shows that the level mostly achieved by Islamic Senior High School students is Level 2 (51.4%).